Advanced clinical interpretation of the Delis-Kaplan Executive Function System: multivariate base rates of low scores. Issue 1 (2nd January 2018) - Karr, Justin E.; Garcia-Barrera, Mauricio A.; Holdnack, James A.; Iverson, Grant L.
Abstract: Objective: Multivariate base rates allow for the simultaneous statistical interpretation of multiple test scores, quantifying the normal frequency of low scores on a test battery. This study provides multivariate base rates for the Delis-Kaplan Executive Function System (D-KEFS).Method: The D-KEFS consists of 9 tests with 16 Total Achievement scores (i.e. primary indicators of executive function ability). Stratified by education and intelligence, multivariate base rates were derived for the full D-KEFS and an abbreviated four-test battery (i.e. Trail Making, Color-Word Interference, Verbal Fluency, and Tower Test) using the adult portion of the normative sample (ages 16–89).Results: Multivariate base rates are provided for the full and four-test D-KEFS batteries, calculated using five low score cutoffs (i.e. ≤25th, 16th, 9th, 5th, and 2nd percentiles). Low scores occurred commonly among the D-KEFS normative sample, with 82.6 and 71.8% of participants obtaining at least one score ≤16th percentile for the full and four-test batteries, respectively. Intelligence and education were inversely related to low score frequency.Conclusions: The base rates provided herein allow clinicians to interpret multiple D-KEFS scores simultaneously for the full D-KEFS and an abbreviated battery of commonly administered tests. The use of these base rates will support clinicians when differentiating between normal variations in cognitive performance and true executive function deficits.